Knowledge, attitude and practices of cardiopulmonary resuscitation among medical interns & junior residents (Panacea Journal of Medical Sciences, 2022)
Background: Cardiopulmonary resuscitation (CPR) is a lifesaving technique that's useful in many emergencies. There is documented evidence that timely performed CPR can prevent sudden death. The quality of CPR depends on the sufficiency of the knowledge of health professionals, with this background the present study was undertaken to assess knowledge, attitude and practice of Cardiopulmonary Resuscitation among Junior Residents and Medical interns.Materials and Methods: It is a cross-sectional study conducted from October to December 2018 among 100 medical interns and junior residents of a tertiary care institute in Karnataka. A Pre tested structured questionnaire was used to assess the knowledge, attitude and practice among the study participants.Results: The mean knowledge score of MBBS interns was 22.63±4.211 and the mean score of junior residents was 22.06 ± 3.788. Out of the total, 52% of study subjects had fair knowledge, 36% had good knowledge score and only 8% had poor knowledge score. Almost all (90%) the participants had positive attitude towards CPR, 63% of study participants had assisted while performing CPR and 34% had performed CPR independently.Conclusions: The knowledge, attitude and practices of cardiopulmonary resuscitation among the medical interns and junior residents is better in the present study compared to studies conducted in other parts of India. Simulation based training and exposure to more number of CPR practices in real scenarios will further boost up their confidence to perform this life saving technique.